Pemberdayaan Ekonomi Masyarakat disekitar Obyek Wisata Taman Nasional Sebangau Kelurahan Kereng Bangkirai Kota Palangka Raya - Lia Sabtuti; Yunikewaty; Tresia Kristiana (Journal of Environment and Management, 2020)
This study aims to examine the economic empowerment program to villagers around Sebangau National Park, Kereng Bangkirai Sub district, Palangka Raya City as well as economic advantages the gain. We also proposed strategies to improve community economic empowerment around the tourist attraction in the park. A qualitative research type with inductive approach was used to analyze data collected from government, tourism organizers, visitors and the commu-nity. The results show the economic empowerment of the community around the National Park has been going well. Items provided by the villagers around Kereng Bangkirai jetty, among others are, traditional boat attraction, household handicraft or products such as purun hat, traditional beverages, traditional food and dried fish, photo booths, and oth-er community activities under the supervision of local social office. The promotion of tourist attraction and tourism products were done through many social media platforms. Villagers who involved in tourism attractions or providing service or unique goods earned varied incomes, depending on types of service or goods the offered. The amount of money they earn, however, still below the regional minimum wage in Central Kalimantan, although still meet their daily needs. The further economic empowerment can be achieved by improving human resources through skill training for villagers, providing them with knowledge to attract more visitors and boosting local potential. Enhancing local institu-tion who act as the main actor in the tourism management of Sebangau National Park is also urgent to do.